Should brain chip implants for memory and cognitive enhancement be banned in competitive national examinations? - Chin, Alexis Heng Boon; Alsomali, Nimah; Muhsin, Sayyed Mohamed (Springer, 2024)
In a recent medical breakthrough, Elon Musk’s startup company Neuralink implanted the first brain chip in a human patient, purportedly for aiding paralysis. While certainly representing a significant medical milestone for many patients afflicted with debilitating brain and spinal cord injuries, as well as devastating neurodegenerative diseases such as Parkinson’s and Alzheimer’s, it must be noted that this very same technology can also be manipulated for human memory or cognitive enhancement. What happens if a brain chip were to be developed that can significantly improve either IQ (intelligence quotient) or memory, and these were then implanted in people to enhance their performance in highly competitive national examinations for college entrance or gaining employment in civil service positions? This article therefore discusses the ethical implications of this nascent technology platform, and whether its use in competitive national examinations should be banned.